A warrant for pain: caveat emptor vs. the duty of care in American medicine, c. 1970-2010 - Offer, A (University of Oxford, 2012)
Bad ethics can make for bad economic outcomes. Bad ethics are defined hedonically as the infliction of pain on others for private advantage. The infliction of pain is often justified by ‘Just World Theories’, which state that everyone gets what they deserve. Market liberalism (and its theoretical underpinning in neoclassical economics) is one theory of this kind. As an example, the micro and macro underperformance of the American health system c. 1970-2010 is explained in terms of the shift in policy norms from the fiduciary norm "first do no harm" to the neo-liberal market norm of "let the buyer beware" (caveat emptor) since the 1970s.